English Shaming on TikTok: A Window into English Language Ideologies in Indonesia - Nakita Febiola Vesya; Mohammad Umar Muslim (Universitas Islam Negeri Palopo, 2025)
In Indonesia, positive opinions of English are frequently linked with instances of mockery aimed at those thought to have poor English skill. This practice is known as English shaming and has gained importance in the modern era of social media. This study aims to identify English language ideologies in Indonesia through the lens of online English shaming. Using a qualitative research approach based on virtual ethnography, this study draws on the theoretical frameworks of language ideology. Analysis of 621 comments on TikTok is carried out using a three-stage inductive coding process drawn from the Constructivist Grounded Theory methodology. The findings suggest that there are four key English language ideologies in Indonesia: 1) non-standard English is unacceptable; 2) English is an index of educational level; 3) non-standard English is acceptable, and 4) non-standard use of English in international forum is national disgrace. These findings highlight the dominant role of